Effects of Monosodium Glutamate (MSG) intake during pregnancy and lactation on calcium levels in the teeth and alveolar bones of rat offspring - Taqwim, Ali; Noor, Anggita Rizky Rizali; Wati, Erna Kusuma; Ramadhani, Amilia (Faculty of Dentistry, Universitas Gadjah Mada, 2024)
Monosodium glutamate (MSG) is a widely used food additive that enhances flavor. However, excessive MSG intake during pregnancy and lactation may pose health risks to both the mother and the developing fetus, particularly in terms of tooth and bone development. This study aimed to investigate the effect of maternal oral administration of MSG during pregnancy and lactation on calcium levels in the teeth and alveolar bones of rat offspring. This research is a laboratory experiment with a post-test-only control group design. Thirty pregnant Sprague Dawley rats were randomly allocated into three groups: a control group receiving distilled water and two treatment groups receiving MSG at doses of 3 mg/g BW and 6 mg/g BW, respectively. MSG was administered orally from the 5th day of pregnancy until the end of the lactation period. The calcium levels in the teeth and alveolar bones of the offspring were measured using atomic absorption spectrophotometry (AAS). Data were analyzed using one-way ANOVA and post hoc LSD. The mean calcium levels in the teeth and alveolar bones of the offspring in the MSG treatment groups were significantly lower than those in the control group (p < 0.05). The reduction in calcium levels was dose-dependent, with the higher MSG dose (6 mg/g BW) resulting in a more pronounced decrease compared to the lower dose (3 mg/g BW). Maternal MSG intake during pregnancy and lactation leads to a dose-dependent decrease in calcium levels in rat offspring’s teeth and alveolar bones, suggesting that excessive MSG intake during these critical periods potentially leads to impaired tooth and bone development.